2007
DOI: 10.1177/0748233707080906
|View full text |Cite
|
Sign up to set email alerts
|

900 MHz radiofrequency-induced histopathologic changes and oxidative stress in rat endometrium: protection by vitamins E and C

Abstract: There are numerous reports on the effects of electromagnetic radiation (EMR) in various cellular systems. Mechanisms of adverse effects of EMR indicate that reactive oxygen species (ROS) may play a role in the biological effects of this radiation. The aims of this study were to examine 900 MHz mobile phone-induced oxidative stress that promotes production of ROS and to investigate the role of vitamins E and C, which have antioxidant properties, on endometrial tissue against possible 900 MHz mobile phone-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 45 publications
2
45
1
2
Order By: Relevance
“…Similar protective role of vitamin E against EMFs induced oxidative stress was previously reported in different tissues [14,31]. The protection by vitamin E may also due to the reduction of lipid peroxidation.…”
Section: Resultssupporting
confidence: 62%
“…Similar protective role of vitamin E against EMFs induced oxidative stress was previously reported in different tissues [14,31]. The protection by vitamin E may also due to the reduction of lipid peroxidation.…”
Section: Resultssupporting
confidence: 62%
“…Studies carried out by Guney et al on rats exposed to the frequency 900 MHz proved that these ranges of waves cause the occurrence of oxidative stress leading to an inflammatory state of the endometrium [44]. These studies demonstrated that among irradiated rats a decrease was noted in the endometrial superoxide dismutase (SOD) and catalase, and this phenomenon may be inhibited by the supplementation of vitamins C and E.…”
Section: Mechanisms Of the Effect Of Emrmentioning
confidence: 87%
“…Grundler et al were the first to demonstrate that EMW induce free radical activity in cells (47,48). Animal studies have shown various examples of cell phone induced OS in the eyes, brain, kidneys and endometrial lining of uterus (48,(49)(50)(51)(52). Most recently, Kesari et al have also shown a significant increase in ROS level in the semen of male rats exposed to mobile phone (58.25 ± 10.36 mg/L) as compared with the semen of sham exposed animal (41.78 ± 12.93 mg/L) (P = 0.035) (40).…”
Section: A -Oxidative Stressmentioning
confidence: 99%